A new status and combination in a Madagascan Kalanchoe, K. beauverdii var. juelii (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2019)
With about 60 of the c. 150 known species of the genus Kalanchoe Adanson (1763: 248) sensu lato having been recorded from Madagascar, this island is the present-day centre of diversity of the genus (Smith & Figueiredo 2018). When Rauh & Hebding in Rauh (1995: 15) suggested the reclassification of the Madagascan K. juelii Raymond-Hamet & Perrier de la Bâthie (1914: 135, as ‘jueli’) as a variety of K. beauverdii Hamet (1907: 887), they did not cite the basionym, with the result that their proposed new combination, ‘Kalanchoe beauverdii Raym.-Hamet var. juelii, as ‘jueli’(Raym.-Hamet & H.Perrier) Rauh & Hebding’, was not validly published (Art. 41.5 of the ICN, Turland et al. 2018).